Implementasi Kurikulum Merdeka di Lembaga Pendidikan Era Perkembangan Teknologi - Agustini, Asri (Journal of Innovation in Teaching and Instructional Media, 2025)
The government policy of implementing the independent curriculum as part of the National Education system certainly has great challenges and opportunities in the era of technological development, where knowledge and technology are developing very rapidly, resulting in rapid and competitive changes. Therefore, the implementation of the independent curriculum must be aligned and supported by good resources, the strength of financial institutions, support and guidance from stakeholders. The purpose of this study was to analyze the effectiveness of the implementation of the independent curriculum to face technological developments. This study uses a qualitative descriptive method. Data collection tools use interviews, documentation, and literature reviews. The results of the study stated that 1) The implementation of the independent learning curriculum consists of School Assessment; surprising characters; effective RPP and zoning system; 2) The challenges of implementing the independent curriculum in facing further technological developments to the implementation of learning include the demand for continuous improvement of teacher competence; the need for adequate facilities and infrastructure; and the demand for the independence of educational institutions.